Post occupancy evaluation (POE) of industrial building systems : analysis of occupancy satisfaction / Bintulhuda Zainodin and Natasha Khalil - Zainodin, Bintulhuda; Khalil, Natasha (2019)
Sustainable construction is one of the increasing areas in transforming a better field for Malaysian construction industry. Industrialized Building System (IBS) is one of the approach in achieving sustainable construction that able to deliver built-up assets to enhance the quality of life, fulfills customer's satisfaction and maximize the efficient use of resources. However, despite its benefits, there are several issues in regards to the IBS constructed buildings after it is handed over to the client. Among the issues are delivery of leads to poor workmanship and poor building conditions that leads to discomfort and dissatisfaction of the building occupants. Post Occupancy Evaluation (POE) is known as the method that able to benchmark the performance of building by incorporating occupants' feedback towards the building's poor condition. Therefore, this paper aims to determine the performance criteria and satisfaction level of occupants in IBS building towards performance improvement. Quantitative approach is used in this study where questionnaire is used as the main instrument. College Beta in UiTM Tapah campus is chosen as the sample building and the questionnaires were distributed to the hostel residents. The outcome of this study has contributed and enhanced ways towards performance improvement using POE method.